GENETIC VARIABILITY STUDIES IN PIGEONPEA [Cajanus cajan (L.) Millsp.] - JAKE LEE GALIAN, NIDHI MOHAN, C.V. SAMEER KUMAR AND P. MALLESH, (The Journal of Research ANGRAU, 2015)
Thirty-nine pigeonpea genotypes were evaluated for variability, heritability and genetic advance under rainfedcondition during Kharif 2015 at International Crop Research Institute for Semi-Arid Tropics (ICRISAT). The analysis ofvariance showed significant differences among the genotypes for all the characters studied, indicating that there washigh variability among the genotypes. Grain yield (t ha-1) has exhibited high genotypic and phenotypic coefficient ofvariation, thus indicates that this character is governed by genetic factors and possible improvement through selection.Whereas, plant height, number of primary branches plant-1, number of secondary branches plant-1, number of podsplant-1 and 100-seed weight obtained moderate estimates at both levels. This may imply that there is a scope ofimprovement in these characters. High heritability combined with high genetic advance as percent of mean wasobtained for characters viz., days to 50% flowering, plant height, number of primary branches plant-1, number ofsecondary branches plant-1, no. of pods plant-1, 100-seed weight and grain yield (t ha-1). This indicates that theheritability was due to additive gene effects and selection would be promising for these characters